Two unknown music fragments in the Grey Collection of the South African Library Cape Town - Steyn, C. (South African Journal of Cultural History, 2012)
Among the Medieval and Renaissance manuscripts in the Grey Collection in the National Library in Cape Town there are two fragments with music notation, one large, one small. Although research has been done on most of the music manuscripts in the Collection, these fragments have not been studied before. Fragments of Medieval and Renaissance manuscripts have been neglected in scholarly research, but recently serious studies have been made have been made in several overseas centres. Of the two fragments discussed in this article, the smaller one, consisting of only two folios, is the more interesting. It forms part of an earlier binding of MS Grey 3c16, a 15th century copy of Guido delle Collone's Historia destructionis Troiae, and although no date or provenance is mentioned in the fragments, it has been possible to establish that it was a 12th century noted missal that had probably belonged to Dryburgh Abbey, a Premonstratensian monastery on the Scottish border. Early noted missals in which chants, readings and prayers appear in the correct liturgical order, as in this fragment,are very rare. The larger fragment, MS 48b3, consists of 43 leaves and is very well preserved and attractive with many decorative initials in bright colours. It formed part of the sanctorale of a very large choir book and was possibly in use in the Bologna region of Italy in the 15th century. A more precise dating and provenance could not be established, however. Twee onbekende musiekfragmente in the Grey-versameling van die Suid-Afrikaanse Biblioteek, Kaapstad Onder die Middeleeuse en Renaissance manuskripte in die Grey-versameling in die Nasionale Biblioteek in Kaapstad is twee fragmente met musieknotasie die een groot, die ander klein. Hoewel navorsing oor die meeste van die musiekmanuskripte in die versameling gedoen is, is hierdie fragmente nog nie vantevore bestudeer nie. Fragmente van Middeleeuse en Renaissance manuskripte is grootliks in akademiese navorsing verontagsaam, maar onlangs is deurdringende navorsing in verskeie oorsese sentra gedoen. Van die twee fragmente wat in hierdie artikel bespreek word, is die kleiner een, wat slegs twee folios beslaan, die interessantste. Dit vorm deel van 'n vroeer omslag van MS Grey 3c16, 'n vyftiende-eeuse kopie van Guido delle Collone se Historiade structionis Troiae, en hoewel geen datum of herkoms in die fragment genoem word nie, was dit moontlik om vas te stel dat dit 'n twaalfde-eeuse genoteerde missaal was wat waarskynlik aan die Dryburgh Abdy, 'n Premonstratensiese monnikeklooster op die grens van Skotland behoort het. Vroee genoteerde missale waarin die gesange, lesings en gebede soos in hierdie fragment in die korrekte liturgiese volgorde verskyn, is baie skaars. Die groter fragment, MS 48b3, bestaan uit 43 blaaie en is goed bewaar en aantreklik met baie dekoratiewe hoofletters in helder kleure. Dit vorm deel van die sanktorale van 'n baie groot koorboek en is moontlik in die vyftiende eeu in die Bologna-streek van Italie gebruik. 'n Meer presiese datum en herkoms kon egter nie vasgestel word nie.
Keywords: dryburgh

Dryburgh Abbey (Mertoun Parish) - Murray, David (Discovery and Excavation in Scotland: A’ Lorg agus a' Cladhach an Albainn, 2009)
Keywords: dryburgh

Dryburgh Abbey (Mertoun Parish): Watching Brief/Excavation/Standing Building Recording - Murray, David; Radley, Alan (Discovery and Excavation in Scotland: A’ Lorg agus a' Cladhach an Albainn, 2009)
Keywords: dryburgh

Dryburgh Abbey (Mertoun parish): Watching Brief - Hollinrake, A. (Discovery and Excavation in Scotland, 2004)
Keywords: dryburgh

Dryburgh Abbey (Mertoun Parish) (Discovery and Excavation in Scotland, 2003)
Keywords: dryburgh

Dryburgh Abbey (Mertoun parish): Excavation - Ewart, G.; Radley, A.; Murray, D. (Discovery and Excavation in Scotland, 2002)
Keywords: dryburgh

Dryburgh Abbey (Mertoun parish): Watching Brief - Stewart, D. (Discovery and Excavation in Scotland, 2000)
Keywords: dryburgh